Menggunakan Metode Etnografi Dalam Penelitian Sosial - Windiani Windiani; Farida Nurul Rahmawati (DIMENSI - Journal of Sociology, 2016)
The purpose of this paper Is to introduce the readers in understanding the steps of ethnograpy use in social research method. This paper was presented about what is ethnograpy, ethnograpy development and debates in practice research,ethnography as a methode and methodological, as well as the steps in conducting ethnography research. The debate over postmodern critique of ethnograpy and also various kinds of ethnography are described in this paper.